Sex differences in treatment and outcome of patients with cardiogenic shock complicating acute myocardial infarction. (2nd May 2022) - Holle, S; Josiassen, J; Helgestad, OKL; Schmidt, H; Holmvang, L; Jensen, LO; Ravn, HB; Moeller, JE; Fosboel, EL; Thoegersen, M; Hassager, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Differences in outcome between men and women among patients with acute myocardial infarction (AMI) have previously been investigated[1–4], while evidence concerning sex differences in patients with AMI complicated by cardiogenic shock (AMICS) is limited. Purpose: The aim of this study was to investigate sex differences in patients with AMICS related to demographics, treatment and long-term outcome. Methods: All adult patients (age ≥18 years) with AMICS hospitalized at one of two tertiary heart centers with a catchment area corresponding to 4 million citizens were included in this study. In the study period from January 1st, 2010 to December 31st, 2017, a total of 1716 AMICS patients were identified following individual validation. Data regarding patient characteristics, treatment and clinical outcome including short-term follow-up were extracted from medical records and an 8, 5-year long-term follow-up were obtained from the national patients registry. A multivariate cox regression model was used to adjust for significant sex differences known to be associated with outcome in AMICS including age and an out-of-hospital cardiac arrest (OHCA) presentation. Results: Of the 1716 included AMICS patients, 438 (26%) were women. Women were older than men, 71±12 years and 66±11 years, P=<0.0001, respectively. Patients characteristics were similar between sex except for hypertension which was more common among women. Women were more often initially admitted to a local hospital (41% women and 30% men, P=<0.0001), while more men presented with OHCA (25% women and 48% men, P=<0.0001), which persisted after adjustment for age. At the time of shock development, women and men were comparable regarding blood pressure (mean: both 82 mmHg, P=0.44), heart rate (mean: 88 vs. 85 bpm, P=0.10), p-lactate (median: 5.2 vs. 5.5 mM, P=0.07), and left ventricular ejection fraction (median: both 30%, P=0.11). However, fewer women were treated with mechanical circulatory support (19% women and 26% men, P=0.002), which persisted following multivariate adjustment. Additionally, women were associated with a lower use of acute revascularization (83% women and 88% men, P=0.006) including percutaneous coronary intervention (n=1405) and coronary artery bypass graft (n=101) and mechanical ventilation (67% women and 82% men, P=<0.0001). These significant signals did not remain following cox regression analysis. Women had a significantly higher short-term as well as long-term mortality rate, which persisted in the multivariate model (Figure 1). Conclusion: Women were associated with lower use of mechanical circulatory support devices among AMICS patients. Women had a significantly higher short- and long-term mortality rate compared to men.